Relationships between pulmonary oxygen uptake kinetics and other measures of aerobic fitness in middle- and long-distance runners - Kilding, A. E.; Fysh, M.; Winter, E. M. (European Journal of Applied Physiology, 2007)
The purpose of this study was to assess the relationships between on- and off-transient pulmonary oxygen uptake kinetics and other measures of aerobic fitness in middle-distance (MD) and long-distance (LD) runners. 16 MD and 16 LD runners participated and each completed a series of tests to determine their maximal oxygen uptake ([(V)\dot]O2 max),(VO2max) gas-exchange threshold (GET), running economy (RE) and the primary time-constant for [(V)\dot]O2VO2 at the onset (ton) and offset (toff) of moderate-intensity treadmill exercise. Relationships between measures were established using Pearson product moment correlations (r). The relationships between [(V)\dot]O2VO2 kinetic parameter and other aerobic measures varied depending on classification of runner (MD or LD runner). There was a significant relationship between [(V)\dot]O2maxVO2max and ton and toff in LD runners (ton: r = -0.70, P = 0.003; toff: r = -0.55, P = 0.029), but not for MD (ton: r = 0.24, P = 0.366; toff: r = -0.09, P = 0.739). Similar relationships also existed between GET, RE and kinetic parameters for LD but not MD runners. The inconsistent relationships between [(V)\dot]O2VO2 kinetic parameters and other measures of aerobic fitness in MD and LD runners is intriguing. Further work is now required to identify how the volume and intensity of training influence peripheral adaptations in Type I and Type II fibres and how these may, or may not influence [(V)\dot]O2VO2 kinetic responses in the moderate- and heavy-intensity domain.